Risk Stratification and Personal Protective Equipment Use in Pediatric Endoscopy During the Coronavirus Disease 2019 Outbreak: A Single-center Protocol. Issue 6 (June 2020) - Say, Daphne S.; de Lorimier, Arthur; Lammers, Cathleen R.; Natale, JoAnne; Lakshminrusimha, Satyan; Wiedeman, Jean; Partridge, Elizabeth
Abstract : ABSTRACT: SARS-CoV-2, the novel coronavirus causing coronavirus disease 2019 (COVID-19), is now a global pandemic. Human-to-human transmission has been documented to occur through respiratory secretions, feces, aerosols, and contaminated environmental surfaces. Pediatric patients present a unique challenge as they may have minimal symptoms and yet transmit disease. Endoscopists face risk for infection with viruses like SARS-CoV-2, as the aerosol generating nature of endoscopy diffuses respiratory disease that can be spread via an airborne and droplet route. We describe our center's methodology for pediatric patient risk stratification to facilitate responsible use of endoscopic resources during this crisis. We also describe our recommendations for use of personal protective equipment by endoscopists, with the goal of ensuring the safety of ourselves, our anesthesiology and endoscopy staff, and our patients.